(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Show “Revista Íntima”, by La Vaca Companhia de Artes Cênicas. Dramaturgy by Afonso Nilson. Directed by Vicente Concílio. With the actresses: Drica Santos and Milena Moraes.